Professional women in South African Pentecostal Charismatic churches - Frahm-Arp, Maria (Studies of religion in Africa 0169-9814, 2010)
This book gives a unique insight into the changing shape of contemporary religion examining the new role that Pentecostal Charismatic Christianity plays in the lives of young, professional, black women who are enjoying career success and becoming part of South Africa's new middle class. Amongst these women an interesting relationship has emerged between work and religion as they feel that the social networks and self confidence they gain from their religious communities are as important as their spiritual experiences. But not all the women who join these churches remain, and this book explores